FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN LUARAN PENDERITA INFEKSI SUSUNAN SARAF PUSAT DI BANGSAL RAWAT INAP ALAMANDA RSUD Dr. Hi. ABDUL MOELOEK PROVINSI LAMPUNG - Assidiq, Hans Pratama; Perdani, Roro Rukmi Windi; Darwis, Iswandi; Berawi, Khairun Nisa (Medula, 2024)
Infection of the Central Nervous System is a disease that can cause death and serious disability if not detected and treated appropriately. Meningitis was a specific cause of death for children under 5 years old during 2000-2013. In the Alamanda Inpatient, RSUD Dr. Hi. Abdul Moeloek, Lampung Province, during 2020-2021 there were 50 cases of CNS infections. The aim of this study was to determine the factors associated with the outcomes of CNS infection sufferers in the Alamanda Inpatient, RSUD Dr. Hi. Abdul Moeloek, Lampung Province. This research uses an observational analysis method with a cross sectional research design. The population of this study were pediatric patients with a medical diagnosis of central nervous system infection at the Alamanda Inpatient, RSUD Dr. Hi. Abdul Moeloek, Lampung Province, for the period January 2020 – May 2021, totaling 50 patients with a total sample population. Univariate analysis showed that 39 sufferers of CNS infections in the Alamanda Inpatient, RSUD Dr. Hi. Abdul Moeloek, Lampung Province, mostly aged > 1 year as much as 79.6%, male as much as 51.3%, type of infection is meningitis or encephalitis as much as 66.7%, GPCS score not comatose 79.5%, normal nutritional status 69.2%, long hospitalization >5 days 69.2% and survival outcome is 82.1%. Bivariate analysis using the Chi-Square test showed that the factors that had the most influence on the outcomes of CNS infection sufferers in the Alamanda Inpatient, RSUD Dr. Hi. Abdul Moeloek, Lampung Province., in order of long hospitalization, GCPS coma score, nutritional status, type of infection, and age. Meanwhile, gender does not influence the outcome of CNS infection sufferers in the Alamanda Inpatient, RSUD Dr. Hi. Abdul Moeloek, Lampung Province.